Advancing breastfeeding promotion: leveraging integrative natural galactagogues and unveiling their potential roles—Insights from a 19-year Taiwan nationwide registry to address lactation insufficiency in postpartum women - Liao, Chung-Chih; Chien, Chi-Hsien; Hsu, Tzu-Ju; Li, Jung-Miao (Frontiers in Nutrition, 2024)
Lactation insufficiency is a prevalent challenge for nursing mothers globally. There is a growing interest in the use of herbal galactagogues for enhancing lactation, but their therapeutic efficacy and underlying mechanisms need thorough investigation. This study aims to investigate the efficacy and mechanisms of action of herbal galactagogues in addressing lactation insufficiency by utilizing real-world data and employing a network analysis approach. Our retrospective study used Taiwan's Longitudinal Health Insurance Database 2000 (LHID2000) to identify 490 patients diagnosed with lactation insufficiency from 2000 to 2018. We analyzed demographic characteristics, co-existing diseases, and prescription patterns for both users and non-users of Chinese herbal products (CHP). Additionally, we utilized a network analysis approach to explore potential compounds and targets in the most frequently used CHP, the Wang Bu Liu Xing and Lu Lu Tong herb pair (WLHP) combination. Out of 490 patients, 81% were CHP users. There were no significant differences in demographic characteristics between CHP users and non-users, but we observed a notable divergence in the prevalence of co-existing diseases. A detailed examination of CHP prescriptions revealed the predominance of WLHP, prompting further investigation. Comprehensive analysis identified 29 major compounds in WLHP, which were associated with 215 unique targets. Intersection analysis revealed 101 overlapping targets between WLHP and lactation, suggesting their potential as therapeutic targets for lactation insufficiency treatment. Topological analysis of the protein-protein interaction (PPI) network identified 13 hub genes potentially crucial for the therapeutic effect of WLHP.Functional enrichment analysis showed that these targets were involved in critical lactation regulation pathways, including the PI3K-Akt signaling pathway, Prolactin signaling pathway, Estrogen signaling pathway, and AMPK signaling pathway. This study emphasizes the potential of CHP, specifically the WLHP combination, in managing lactation insufficiency. The multi-compound, multi-target approach of WLHP and its interaction with key biological processes and signaling pathways offer valuable insights into the underlying mechanisms of its therapeutic effects. These findings warrant further experimental validation and can guide future research and clinical applications of CHP in lactation insufficiency treatment.